KEBERMAKNAAN BAHASA TUTUR GURU DAN SISWA DALAM PROSES BELAJAR MENGAJAR DI SEKOLAH DASAR : Studi Semantis Penggunaan Bahasa Tutur Dalam Proses Belajar Mengajar - Kosadi Hidayat S, - (1997)
This research is conducted mainly due to the fact that the use of the Indonesian language has rapidly developed in line with the increasing demand for science and technology nowadays. The use of the Indonesian language is so varied depending upon its condition, situation as well as the context of its users. Owing to these, there comes the varieties of the language for examples: the language variety used in offices, agricultures, markets, tourism, education and other contexts. Since the variétés of the language use are so varieted, this study focuses on the use of the Indonesian language at education circumstances only. The same is true with education for university. Therefore, the education level which becomes the object of the study is that of basic education covering: Merdeka Elementary School, Margahayu Raya Elementary School and Cihampelas Elementary School Bandung Municipality. The reasons why those schools are decided to be the object of the study are: 1. The National Set Standard Achievment Test of the three schools are closely related reaching 6,9 on the average; 2. The education qualification of the teachers is generally of SPG graduate; (Teacher's Training for Elementary School) and 3. The distribution of places represents that of town, urban and rural.